Analisis Pengaruh Pajak dan Inflasi Terhadap Pendapatan Nasional: Bukti Empiris Tahun 2018 - 2024 - Doli Syahputra Hasibuan; Lilis Sartika Sihite; Nazwa Aulia; Divo Valentino Siboro (Universitas 45 Surabaya, 2025)
This article aims to analyze the effect of taxes and inflation on national income in Indonesia for the period 2018-2024. This study uses a quantitative method with regression analysis to identify the causal relationship between these variables. Data were obtained from the Central Statistics Agency (BPS) and Bank Indonesia, then processed using IBM SPSS Statistics 30 for Windows. The results of the study indicate that tax revenue has a significant and positive effect on national income, with a very strong contribution. Conversely, inflation also affects state revenue, although it does not affect taxes. The resulting regression equation shows that any increase in tax revenue will increase national income, while inflation also has a positive impact. In conclusion, both taxes and inflation have an important role in influencing Indonesia's national income. This study provides empirical evidence regarding the relationship between the two factors and can be a basis for the government to develop more effective economic policies in increasing national income and strengthening the country's economy.